Rapid increase in the risk of extreme summer heat in Eastern China - Sun, Ying; Zhang, Xuebin; Zwiers, Francis W.; Song, Lianchun; Wan, Hui; Hu, Ting; Yin, Hong; Ren, Guoyu (Nature climate change, 2014)
Mean summer temperature in Eastern China has increased by 0.82 °C since the 1950s and five of the hottest summers have occurred since 2000. This study estimates anthropogenic influence to have caused a greater than 60-fold increase in the likelihood of extreme summer heat and projects that hot summers will continue to increase in frequency. The summer of 2013 was the hottest on record in Eastern China. Severe extended heatwaves affected the most populous and economically developed part of China and caused substantial economic and societal impacts 1 . The estimated direct economic losses from the accompanying drought alone total 59 billion RMB (ref. 2 ). Summer (June–August) mean temperature in the region has increased by 0.82 °C since reliable observations were established in the 1950s, with the five hottest summers all occurring in the twenty-first century. It is challenging to attribute extreme events to causes 3 , 4 , 5 , 6 . Nevertheless, quantifying the causes of such extreme summer heat and projecting its future likelihood is necessary to develop climate adaptation strategies 7 . We estimate that anthropogenic influence has caused a more than 60-fold increase in the likelihood of the extreme warm 2013 summer since the early 1950s, and project that similarly hot summers will become even more frequent in the future, with fully 50% of summers being hotter than the 2013 summer in two decades even under the moderate RCP4.5 emissions scenario. Without adaptation to reduce vulnerability to the effects of extreme heat, this would imply a rapid increase in risks from extreme summer heat to Eastern China.